Ask your own question, for FREE!
Mathematics 37 Online
OpenStudy (anonymous):

Find the solution to the system by the substitution method. Check your answer. 2x - 5y = -1 x - 3y = -3

OpenStudy (anonymous):

huh

OpenStudy (anonymous):

im confused

OpenStudy (anonymous):

2(-3+3y)-5y=-1 -6+6y-5y=-1 y=-1+6 y=5 and now just plug in y=5 to your second equation to get x

Can't find your answer? Make a FREE account and ask your own questions, OR help others and earn volunteer hours!

Join our real-time social learning platform and learn together with your friends!
Can't find your answer? Make a FREE account and ask your own questions, OR help others and earn volunteer hours!

Join our real-time social learning platform and learn together with your friends!